ANALISIS KINERJA ACCOUNT OFFICER DAN LOAN OFFICER SERTA DAMPAKNYA TERHADAP PERKEMBANGAN SIMPANAN DAN PINJAMAN PADA KSP KOPDIT OBOR MAS CABANG AGROBISNIS. - Dasilva, Laurensia Fatmawati; Andia Dekrita, Yosefina; Herdi , Henrikus (Jurnal Projemen UNIPA, 2026)
This study analyzes the performance of Account Officer (AO) and Loan Officer (LO) on the development of savings and loans at Koperasi Simpan Pinjam (KSP) Kopdit Obor Mas, Agrobusiness Branch. The objective of this study is to describe the role of Account Officer (AO) and Loan Officer (LO) in fostering the growth of savings and loan disbursement, as well as to identify the determinant factors influencing the effectiveness of their performance. The analytical method employed is descriptive qualitative using observation, interviews, and documentation techniques. The results indicate that the role of Account Officer (AO) in marketing and mobilizing savings, as well as the role of Loan Officer (LO) in credit feasibility analysis, loan disbursement, and credit monitoring, functions as a dominant factor driving the growth of members’ savings and loans. However, the effectiveness of their performance is constrained by limited human resources and suboptimal credit supervision. Although the operational and service systems have been implemented in accordance with established procedures, strengthening competency and monitoring systems is necessary to transform the performance of Account Officer (AO) and Loan Officer (LO) into a more effective and sustainable contribution to the development of savings and loans.